1996
DOI: 10.1002/j.1551-8833.1996.tb06539.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation: its effect on organic matter

Abstract: Mass spectra obtained using fast atom bombardment provided qualitative information about coagulation's effectiveness under various treatment conditions. Removal of natural aquatic dissolved organic matter (DOM) by conventional coagulation using ferric chloride was investigated. Reverse osmosis was used to isolate DOM from the Suwannee River in southern Georgia and from Lake Allatoona in northwestern Georgia. The two most significant differences between the source waters are pH and organic carbon concentration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 23 publications
5
45
1
Order By: Relevance
“…The apparent exclusion of the amide and aromatic rich OM is surprising given that, according to SUVA measurements in this and previous studies, aromatic OM is preferentially removed from solution through flocculation (Dennett et al, 1996). However, it is possible that the more hydrophobic aromatic OM is prone to partition out of solution phase to form micellar associations within the floc or requires only a very small amount of associated Fe for the purposes of charge balance in order to induce precipitation.…”
Section: Stxm Characterization Of Fresh Floc Materialsmentioning
confidence: 48%
“…The apparent exclusion of the amide and aromatic rich OM is surprising given that, according to SUVA measurements in this and previous studies, aromatic OM is preferentially removed from solution through flocculation (Dennett et al, 1996). However, it is possible that the more hydrophobic aromatic OM is prone to partition out of solution phase to form micellar associations within the floc or requires only a very small amount of associated Fe for the purposes of charge balance in order to induce precipitation.…”
Section: Stxm Characterization Of Fresh Floc Materialsmentioning
confidence: 48%
“…Meanwhile, some common observations exist, including: coagulation removes higher molecular weight and hydrophobic NOM (Dennett et al, 1996;Amy et al, 1992;Jacangelo et al, 1994;Owen et al 1995); ozonation can convert NOM from humic substances to non-humic fractions and from higher-to lower-MW fractions (Chiang et al, 2002;Owen et al, 1995); granular activated carbon (GAC) can remove intermediate or small humic molecules more efficiently (Johannsen et al, 1993), and therefore ozonation after filtration can result in enhanced adsorption capacity of GAC (Amy et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The widely used physicochemical processes in water treatment include activated carbon adsorption and coagulation. Adsorption to hydrolysable coagulants is often very effective in removing acidic and basic components of the dissolved organic matter in natural waters provided pH conditions and dosage are properly controlled (Dennett et al 1996). Randtke and McCarty (1979) assessed the potential of various physicochemical processes for the removal of soluble secondary-effluent organics and demonstrated that activated carbon adsorption is generally the most proficient in removal of soluble organic matter.…”
mentioning
confidence: 99%